Discussão sob as perspectivas técnica, econômica e ambiental do uso de concentradores baseados em lentes de Fresnel em sistemas de geração fotovoltaica - Silvestre, Gustavo (Universidade Federal de São Carlos, 2024)
With the expansion and popularization of photovoltaic energy generation systems, con- sumers classified in group A, whether captive or free, meet a significant portion of their demands. However, depending on the size of these photovoltaic generation systems, the capital requirement for the initial implementation investment can become an obstacle. To overcome this obstacle, an alternative to producing a greater amount of energy involves the use of concentrators based on Fresnel lenses that increase the incidence of sunlight on photovoltaic panels, allowing a reduction in the initial investment. In this study, a comparison is presented between a “traditional” photovoltaic generation system and a photovoltaic generation system with Fresnel lens concentrators with the aim of increasing the efficiency per solar module. This comparative study will be based on the number of photovoltaic panel modules required to generate the same amount of energy, impacting the area needed for the installation of photovoltaic panels and the initial investment costs. Therefore, economic aspects, as well as environmental impact and occupied area, will be compared. It is also emphasized that, in addition to reducing technical and economic requirements, the widespread use of concentrators enables a lower use of scarce resour- ces, such as silicon, due to the smaller size of the photovoltaic panels, as well as greater technical efficiency.
Discussion on the technical, economic, and environmental perspectives of the use of Fresnel lens concentrators in photovoltaic generation systems
Keywords: Análise técnico-econômica; Concentradores; Lentes de Fresnel; Sistema de geração fotovoltaica; Technical and economic analysis; Concentrators; Fresnel lenses; Photovoltaic generation systems; ENGENHARIAS::ENGENHARIA ELETRICA::SISTEMAS ELETRICOS DE POTENCIA